Digital Music Pedagogy on TikTok: A Literature Review Perspective - Joevan Akhdan Ertama; Riyan Hidayatullah; Wahyuningsih, Septiana (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2026)
Objective: This study aims to analyze the behaviors of TikTok users in music learning in today’s fast-paced and interactive digital era, considering that TikTok is widely used both as a source of entertainment and information, leading to diverse and unique patterns of user creativity that influence the music learning process. Method: The research employs a literature review by examining relevant scholarly journals and conducting direct observations of phenomena on the TikTok platform, including analyses of short videos, user comments, collaborations, and the dissemination of music content. Collected data were qualitatively analyzed to identify learning behavior patterns both at the individual and social levels. Results and Discussion: Findings reveal that TikTok provides an easily accessible space for expression and creativity, allowing users to learn music independently while also engaging in social interactions. Learning occurs not only individually but also through discussion, clarification, and collective evaluation of music content circulating on the platform, fostering collaboration, innovation, and deeper understanding. Conclusion: This study confirms that TikTok is not merely an entertainment platform but also an effective tool for music learning in the digital era, supporting both personal and collaborative learning while expanding access, creativity, and user engagement in contemporary music education practices.